ANALYSIS OF OUTPATIENT SATISFACTION LEVELS WITH LABORATORY SERVICES AT RSUD KLUNGKUNG - Diah Prihatiningsih; I Gusti Ayu Agung Diah Dwi Sukma; I Gusti Putu Agus Ferry Sutrisna Putra (PT. Jurnal Center Indonesia Publisher, 2025)
Healthcare services must continuously be improved to provide the best care for the community. Patient satisfaction is the result of patients' evaluations of healthcare services, comparing their expectations with the actual healthcare services received in a hospital setting. Patient satisfaction with laboratory services is not solely determined by the availability of sufficient healthcare personnel but also requires strong commitment and dedication from healthcare workers to provide professional services, supported by adequate facilities and medical equipment. This study aims to assess the level of outpatient satisfaction with laboratory services at RSUD Klungkung. The research employs an observational method with a cross-sectional design. Data collection was conducted using questionnaires, with a sample of 97 respondents selected through purposive sampling. The data analysis in this study was performed using the Chi-Square test. Based on the five service quality dimensions—reliability, responsiveness, assurance, empathy, and tangibles—the results showed a p-value < 0.05. Among these dimensions, responsiveness had the lowest p-value (0.005 < 0.05), indicating its stronger influence. These findings conclude that there is a significant relationship between service quality dimensions and the level of outpatient satisfaction with laboratory services at RSUD Klungkung. Furthermore, the responsiveness dimension, which had the lowest p-value compared to the other four dimensions, indicates that it has the most significant impact on patient satisfaction with laboratory services provided by the staff at RSUD Klungkung.